A history of sport historiography in Brazil: Proceedings of the Brazilian Congress of Sport History, Leisure, and Physical Education (1993-2016) - Honorato, Tony (História da Historiografia: International Journal of Theory and History of Historiography, 2022)
The Brazilian Congress of Sport History, Leisure and Physical Education (CHELEF) is a traditional event in Latin America which has been celebrated for more than 25 years in Brazil. Current paper, focusing on bibliographic production, investigates sport historiography in Brazil as provided by the proceedings of the Brazilian Congress of Sport History, Leisure and Physical Education between 1993 and 2016. Proceedings provided 1517 texts, of which 694 focus on sports. The history of sport historiography took into account themes, source types, historical periods, theory and methodology and the most quoted authors/papers in the texts in the Proceedings. Current sports historiography in Brazil has tried to break away from the legitimization of official narratives which proved to be universals and based on the myth of their origin. New aims, sources and theories of history were required for the social and dynamic conditions of academic events and post-graduate courses.